The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s40463-019-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

Donor site morbidity following radial forearm free flap reconstruction with split thickness skin grafts using negative pressure wound therapy

Abstract: Background Donor site complications secondary to radial forearm free flap (RFFF) reconstruction can limit recovery. Optimizing hand and wrist function in the post-operative period may allow more efficient self-care and return to activities of daily living. Negative pressure wound dressings (NPD) may increase blood flow and perfusion as compared to static pressure dressings (SPD) designed to minimize shear forces during the healing period. This study aims to compare subjective and objective hand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…Five studies reported skin graft complications, and no significant difference in these complications was identified in all studies 28‐31 . Chio et al reported 7 (30.4%) and 12 (44.4%) cases of skin graft complications at 2 weeks after surgery in the NPWT and control groups, respectively 29 .…”
Section: Resultsmentioning
confidence: 98%
“…Five studies reported skin graft complications, and no significant difference in these complications was identified in all studies 28‐31 . Chio et al reported 7 (30.4%) and 12 (44.4%) cases of skin graft complications at 2 weeks after surgery in the NPWT and control groups, respectively 29 .…”
Section: Resultsmentioning
confidence: 98%
“…36 A similar result is seen with the donor area for a free fibula flap, with two studies showing no significant difference in graft take. 25,28 Bach 28 and Clark 36 did, however, find a significantly shorter healing time in the NPWT group-67 days compared with 163 in the bolster dressing group (p<0.02). Kim used a one-stage Alloderm and SSG procedure comparing NPWT with standard dressings and achieved significantly better results.…”
Section: Npwt For Ssgmentioning
confidence: 54%
“…33 The free radial forearm donor site has been studied by multiple groups (Table 2). [34][35][36][37][38] The majority of these studies do not show a significant improvement in graft take, though other advantages have been reported including improved early function. 36 A similar result is seen with the donor area for a free fibula flap, with two studies showing no significant difference in graft take.…”
Section: Npwt For Ssgmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, a randomized controlled trial showed that NPWT significantly improved the appearance of split-thickness skin grafts (STSGs) two weeks after surgery compared with standard packaged dressings (13), and another randomized controlled trial found that NPWT improved the scar color of STSGs (14). In contrast, the results of other randomized controlled trials have indicated that NPWT did not improve the quality or esthetic appearance of scars in STSGs compared with traditional dressings (15).…”
Section: Introductionmentioning
confidence: 99%